Building and Developing a Resilient Community Through Co-Working Space Design: Circular Economy to Circular Space - Ramadhan, Try; Rosadiana, Reina Ayulia; Muhammad Rizki, Luthfi; Widyantoro, Rekso Agung; Adiansyah, Muhammad Arif (Universitas Muhammadiyah Surakarta, 2024)
In the face of challenges affecting society, such as the Covid-19 pandemic, there are negative impacts on social and economic infrastructure, including the labor sector. The response to community vulnerability to disruption is a critical concern that requires resolution. This design-based research aims to provide insights to create and enhance resilient communities through the design of co-working spaces, grounded in sustainable economic principles. Using an exploratory study, problems were identified, and solutions were generated through SWOT and PESTEL analysis. The proposed solutions, involving programs, control measures, architectural considerations, and financial models, were tested through an economic feasibility test approach. The results show that it is possible to implement a sustainable economy in the design of co-working spaces, depending on support from the government and private sectors. Three key aspects-research and development, socio-economic empowerment, and environmental waste management-were formulated to implement the concept, tailored to the potential in each location, using the Covid-19 situation as an illustrative example for future learning and preparedness.